Pemikiran Tasawuf Hamzah Fansuri - Mirza Fauziah (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
This article examines about the personal of Hamzah Fansuri as a tasauf scholars. His thinking is very significant in this field and can be part is very strategic. He lived in the middle of seventeenth century (XVI-XVII) is seen by some scientists as a reformer. He contributed significantly to the development of islamic culture, particularly in the fields of spirituality, philosophy of science, literature and languages at once. Sharp criticism of the political and moral conduct of the kings, Nobles and rich people put him as a courageous intellectual of his time to the palace of Aceh is not so fond of his activities and his followers. Hamzah Fansuri leaving many good works of prose and poetry of sufi. Therefore, his tasauf thinking can be many scientists study.